PHONEME MODIFICATION, CROSS- LINGUISTIC PHONETIC ANALYSIS AND PHONOLOGICAL COMPARISON ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article delves into the modification of phonemes, comparative phonetics, and comparative phonology, offering a comprehensive overview of how sound systems operate across different languages. It begins by explaining the processes that modify phonemes, such as coarticulation, assimilation, and elision, highlighting how sounds can shift depending on their linguistic environment. The article then explores comparative phonetics, focusing on the acoustic and articulatory differences between languages, and how these variations affect the way phonemes are realized in speech. Moving into comparative phonology, the piece examines how phonological systems differ across languages, with an emphasis on phoneme inventories, phonological processes, and the rules governing sound patterns. The article concludes by emphasizing the importance of these studies in understanding both the diversity and commonalities in human language, and how phonetic and phonological comparison helps linguists uncover the cognitive and historical aspects of language evolution. This work is essential for those interested in the intricate relationships between speech sounds, language systems, and linguistic change.